SISTEM PAKAR DIAGNOSA DINI KANKER SERVIKS BERDASARKAN GEJALA PASIEN (STUDI KASUS : RUMAH SAKIT PURI HUSADA TEMBILAHAN) - Loneli Costaner; Samsudin Samsudin (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2014)
Expert system is a system that is trying to adopt human knowledge into a computer, so that the computer can resolve the issue as it is commonly done by experts. Expert systems are typically used for consultation, analysis and diagnosis, assist decision-making, and others. One expert system implementation in the health sector is to perform early diagnosis of the cancer. Cancer is a disease caused by abnormal growth of body tissue cells are transformed into cancer cells. Cancer can affect all levels of society without exception. Many types of cancer that can affect women and is the most deadly cervical cancer. Nearly all the world there are women affected by cervical cancer. This research aims to devise an expert system application for the early detection of cervical cancer which can be used to help the physician or physician's assistant providing information to the public about the dangers posed by cervical cancer as well as forward chaining method with Visual Basic 6.0 programming language and MySQL database. Through this application, users can conduct consultations with the system like a consultation with an expert to detect symptoms that occur on the user as well as finding solutions to the problems faced. Base on the results, 60% of respondents strongly agreed and 47% of respondents agree to the system has been developed. Keyword : Expert System, Cancer Cervix, Forward Chaining